2012
DOI: 10.3109/00952990.2011.643987
|View full text |Cite
|
Sign up to set email alerts
|

Motives and Simultaneous Sedative-Alcohol Use among Past 12-month Alcohol and Nonmedical Sedative Users

Abstract: Findings underscore the need for considering motives in tailoring preventive interventions for reducing SSAU. It may be equally important to direct efforts toward decreasing the number of motives, as well as addressing the specific motives reported for sedative use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
(22 reference statements)
1
10
0
Order By: Relevance
“…Many individuals with benzodiazepine misuse report multiple motives for misuse (McCabe et al, 2009). Misusing benzodiazepines for multiple reasons is particularly common among those with opioid use and/or injection drug use (Fatseas et al, 2009;Vogel et al, 2013), which is consistent with findings that reporting multiple motives is associated with greater substance use severity (e.g., greater benzodiazepine use frequency [McCabe et al, 2009;Nattala et al, 2011]; co-ingesting benzodiazepines and alcohol [Nattala et al, 2012]). Among those with opioid use and/or injection drug use, benzodiazepines are commonly misused to enhance the effects of opioids or opioid agonist medications (see Section 3.4.5.).…”
Section: Route Ofsupporting
confidence: 72%
See 1 more Smart Citation
“…Many individuals with benzodiazepine misuse report multiple motives for misuse (McCabe et al, 2009). Misusing benzodiazepines for multiple reasons is particularly common among those with opioid use and/or injection drug use (Fatseas et al, 2009;Vogel et al, 2013), which is consistent with findings that reporting multiple motives is associated with greater substance use severity (e.g., greater benzodiazepine use frequency [McCabe et al, 2009;Nattala et al, 2011]; co-ingesting benzodiazepines and alcohol [Nattala et al, 2012]). Among those with opioid use and/or injection drug use, benzodiazepines are commonly misused to enhance the effects of opioids or opioid agonist medications (see Section 3.4.5.).…”
Section: Route Ofsupporting
confidence: 72%
“…The finding that self-treatment or coping motives are the most common reasons for benzodiazepine misuse has been replicated across heterogenous samples (see Supplementary Materials). However, benzodiazepines are also misused out of curiosity (Chen et al, 2011;Kapil et al, 2014;Kokkevi et al, 2008;Liebrenz et al, 2015) and for recreational motives, such as to get high (Boyd et al, 2006;Brandt et al, 2014b;Calhoun et al, 1996;Johnston and O'Malley, 1986;Kecojevic et al, 2015a;Kelly et al, 2015b;McCabe et al, 2009;McLarnon et al, 2014;Nattala et al, 2011;Nattala et al, 2012;Quintero et al, 2006;Rigg and Ibanez, 2010;Silva et al, 2013a;Terry-McElrath et al, 2009) and to modify the effects of other substances (Section 3.4.5.). Notably, those who report recreational motives also display more problematic use, such as combining benzodiazepines with other substances, reporting greater substance use severity, taking higher doses, taking benzodiazepines by nonoral routes of administration, and illicitly purchasing benzodiazepines (Fatseas et al, 2009;McCabe et al, 2009;McCabe and Cranford, 2012;McLarnon et al, 2014;Stein et al, 2016).…”
Section: Route Ofmentioning
confidence: 99%
“…Teter et al [12] also found that depression and NMU of prescription stimulants are linked. Nattala et al [33] found that relieving stress and changing mood were the top two motivations for nonmedical prescription sedative and alcohol use among a community-recruited adult population. Here, the temporality of depressed mood was not assessed, so it is unclear if the depressed mood was a result of or a predictor of NMU of stimulants.…”
Section: Discussionmentioning
confidence: 99%
“…Nattala and colleagues (2012) conducted the only study of adult nonmedical sedative use (including benzodiazepines) with co-ingestion; there, 61% of nonmedical users co-ingested a sedative and alcohol, and co-ingestion users were younger, more likely to have used marijuana, and more likely to have recreational motives (Nattala, et al, 2012). …”
Section: Introductionmentioning
confidence: 99%